2021
DOI: 10.3389/fchem.2021.693813
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electroluminescence Based on a π-Conjugated Heptazine Derivative by Exploiting Thermally Activated Delayed Fluorescence

Abstract: Heptazine derivatives have attracted much attention over the past decade by virtue of intriguing optical, photocatalytic as well as electronic properties in the fields of hydrogen evolution, organic optoelectronic technologies and so forth. Here, we report a simple π-conjugated heptazine derivative (HAP-3DF) possessing an n→π* transition character which exhibits enhanced electroluminescence by exploiting thermally activated delayed fluorescence (TADF). Green-emitting HAP-3DF shows relatively low photoluminesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Subsequently, the OLED containing 8 wt % HAP-3MF:mCP showed a pretty high EQE of 11.3% with a low roll-off, demonstrating the efficient harvest of triple exciplex excitons through reverse intersystem crossing (RISC) from T 1 to S 1 under electrical excitation. By changing the three substituents of heptazine core from 2-fluorotoluene to 1,3difluorobenzene, 2,5,8-tris(2,4-difluorophenyl)-1,3,4,6,7,9,9bheptaazaphenalene (HAP-3DF, Figure 2) was obtained (Li et al, 2021). The OLED incorporating 8 wt% HAP-3DF:mCP as an emitting layer exhibited a reasonably high EQE of 10.8%.…”
Section: Thermally Activated Delayed Fluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the OLED containing 8 wt % HAP-3MF:mCP showed a pretty high EQE of 11.3% with a low roll-off, demonstrating the efficient harvest of triple exciplex excitons through reverse intersystem crossing (RISC) from T 1 to S 1 under electrical excitation. By changing the three substituents of heptazine core from 2-fluorotoluene to 1,3difluorobenzene, 2,5,8-tris(2,4-difluorophenyl)-1,3,4,6,7,9,9bheptaazaphenalene (HAP-3DF, Figure 2) was obtained (Li et al, 2021). The OLED incorporating 8 wt% HAP-3DF:mCP as an emitting layer exhibited a reasonably high EQE of 10.8%.…”
Section: Thermally Activated Delayed Fluorescencementioning
confidence: 99%
“…This work demonstrated that the n→π* emitter is a new TADF material and can be applied to OLED applications. Interestingly, the n→π* based HAP-3DF exhibited a lower PLQE of 0.16 and an EQE of 3.0%, illustrating that the subtle structural change has a great influence on luminescence properties (Li et al, 2021). According to the energy gap law, the design of efficient red-emitting materials is rather difficult.…”
Section: Thermally Activated Delayed Fluorescencementioning
confidence: 99%
“…In order to obtain a small ∆E ST and efficient TADF emitters, molecules featuring electron donor-acceptor strcutures are very popular and effective. Thereinto, the heptazine core, which has a considerably planar and rigid heterocyclic system of six C = N bonds surrounding a central sp 2 -hybridised N-atom, is an ideal strong electron acceptor [19][20][21][22]. To the best of our knowledge, several highly efficient heptazine-based red and green TADF emitters have been reported [22][23][24][25], while there are no published heptazine-based blue or deep-blue TADF emitters.…”
Section: Introductionmentioning
confidence: 96%
“…Since the realization of the first organic light-emitting diode (OLED) possessing a high brightness of >1,000 cd m −2 and a low-driving voltage ( V on ) of <10 V ( Tang and VanSlyke, 1987 ), OLEDs based on small molecules ( Tang et al, 1989 ; Adachi et al, 1990 ), polymers ( Burroughes et al, 1990 ; Peng et al, 1998 ), and metal–organic complexes ( Baldo et al, 1998 ; Chang et al, 2013 ) have attracted tremendous attention in the fields of lighting and displays over the past few decades owing to their fascinating merits such as thinness, fast response, and flexibility ( Hong et al, 2021 ). Among these OLEDs, several different kinds of luminescence mechanisms, including traditional fluorescence ( Friend et al, 1999 ; Huang et al, 2012 ), phosphorescence ( Bernhard et al, 2002 ; Zhou et al, 2014 ), triplet–triplet annihilation (TTA) ( Fukagawa et al, 2012 ; Jankus et al, 2013 ), traditional thermally activated delayed fluorescence (TADF) ( Endo et al, 2011 ; Uoyama et al, 2012 ; Zhang et al, 2012 ; Li et al, 2013 ; Li et al, 2021d ), hyperfluorescence ( Nakanotani et al, 2014 ; Chan et al, 2021 ), singlet–triplet inversion ( Ehrmaier et al, 2019 ; Pollice et al, 2021 ; Li et al, 2022 ), exciplex-based TADF ( Goushi et al, 2012 ; Li et al, 2014 ; Oh et al, 2015 ; Li et al, 2021c ; Gu et al, 2022 ), aggregation-induced emission (AIE)–based TADF ( Peng and Shuai, 2021 ; Suman et al, 2021 ), and multiple resonance (MR)–based TADF ( Lee et al, 2020 ; Stavrou et al, 2021 ; Wu et al, 2021 ; Zou et al, 2022 ) have been reported. Thus, the exciplex used to be considered an important reason for poor OLED performance, and it thus should be avoided and eliminated ( Adachi et al, 1990 ; Jenekhe, 1995 ; Morteani et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%